Redesigning Executive Incentives: The Rising Role of Subjective Performance Measures - Fox, Zackery D. (The Accounting Review, 2026)
ABSTRACT Despite the growing use of subjective performance incentives used in executive bonuses, empirical evidence on their effectiveness remains inconclusive. This study explores three aspects of subjective metrics in bonus plan design: their prevalence, the goals they target, and their impact on managerial behavior and firm outcomes. First, I document 53.8 percent of CEO bonus plans include at least one subjective performance measure, and among these plans, an average of 38.9 percent of total bonus weight is allocated to these measures. Using machine learning, I show subjective metrics target incentives related to employees, firm culture, and executive performance. Second, using the Tax Cuts and Jobs Act as a quasi-exogenous shock to contract design, I find firms increase the number and weight of subjective metrics by 22.9 percent and 10.4 percent, respectively. Finally, I find the increasing prevalence of subjective performance measures positively influences CEO effort, corporate culture, and innovation. Data Availability: The data used in this study are from public sources and available upon request. JEL Classifications: M12; J33; G38; M41; H2.